ANALISIS POTENSI SEKTOR UNGGULAN DAERAH KABUPATEN DAN KOTA DI PROVINSI BENGKULU TAHUN 2014-2018 - Anggara, Jaka; Hutapia; Ridwan, Mochamad (UNIB Press, 2022)
Research objectives; to determine the potential of the leading sector, prime sector, and the condition of the economic structure in the Regency and City in Bengkulu Province. The analytical methods used are static and dynamic LQ, Klassen typology and Shift Share. The results showed that the government administration sector, defense and compulsory social security were the leading sectors and a policy priority for the South Bengkulu, Central Bengkulu, Seluma and Kepahiang; the manufacturing sector is a leading sector and a policy priority for North Bengkulu and Mukomuko; the health service sector and activities are the leading sector and become a policy priority for the City of Bengkulu; wholesale and retail trade, car and motorcycle repairs are the leading sectors and are a priority for Rejang Lebong Regency's policies; the construction sector is a leading sector and is a priority for Kaur; and the electricity and gas procurement sector is a leading sector and a policy priority for Lebong. Keyword: Leading Private Sectors; Gross Regional Domestic Produck; A Combined Analysis Of SLQ And DLQ; Klassen Typology And Shift Share Analysis